Effect of Business Scale and Social Media Marketing On the Revenue of Halal MSMEs in Nganjuk Regency - Prastiwi, Nur Indah; Ulfa, Vida Maria; Aswad, Muhammad; Adlan, Muhammad Aqim (Indonesian Journal for Entrepreneurial Review, 2026)
This research is motivated by the development of Halal MSME income through ownership of halal certification based on Government Regulation (PP) No. 39 of 2021, especially in food and beverage management products that have been implemented in Nganjuk Regency. The concentration of this research is on the influence given by the variables of business scale and social media marketing on the income of halal MSMEs both simultaneously and partially. So that a quantitative approach method with an associative research type is used with a total of 77 respondents through data collection procedures using a questionnaire. The conclusion of the analysis of this study shows that even partially, the test results show that the two variables have a significant and positive effect on the income of halal MSMEs accompanied by the acquisition of an R Square value of 83.3%. Thus, it is important for further research to develop other variables/factors, especially the factors most closely related to halal certification